Antara Harga, Promosi, dan Gaya Hidup: Faktor-Faktor Pembentuk Perilaku Konsumtif Mahasiswa di Era Marketplace Digital - Lakuy, Fella; Sopacua, Yustina (Universitas Pattimura, 2025)
This study explores the factors shaping consumptive behavior among university students in the digital marketplace era, focusing on price, promotion, and lifestyle. Triggered by the growing trend of online shopping among students—particularly via Shopee—this research employs a qualitative approach through in-depth interviews with six Communication Science students from the Faculty of Social and Political Sciences at Pattimura University, Ambon. Findings reveal that consumptive behavior is influenced by both internal and external factors in purchase decision-making. Internal factors include product relevance, affordable pricing, attractive promotions (e.g., discounts and cashback), and fast delivery services. External factors encompass cultural values, social interactions, reference group influence, personal lifestyle, and psychological aspects such as motivation and perception. The novelty of this study lies in its comprehensive mapping of digital lifestyle influences on local student consumer behavior, a subject rarely addressed in previous research. These findings contribute to the broader discourse in social sciences and humanities by deepening the understanding of youth digital consumer dynamics. The study highlights the need for digital consumption literacy and critical awareness of online marketing strategies among university students.